2012
DOI: 10.1083/jcb.201106120
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosomes initiate distally and mature during transport toward the cell soma in primary neurons

Abstract: Autophagosome biogenesis and maturation in primary neurons is a constitutive process that is spatially and temporally regulated along the axon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

72
735
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(813 citation statements)
references
References 30 publications
72
735
2
4
Order By: Relevance
“…This model is supported by multiple studies that point to an active process of lysosome biogenesis within axons that begins with the merging of organelles derived from the endocytic and autophagic pathways followed by further maturation toward lysosomes that is coupled to their retrograde transport (44)(45)(46)(47)(48)(49). More specifically, there is a high level of constitutive autophagosome biogenesis that occurs within distal regions of axons (46,48,50,51). These autophagosomes fuse with endosomes and acquire endocytic cargos and late endosome/lysosome marker proteins such as LAMP1 (46,48,49).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This model is supported by multiple studies that point to an active process of lysosome biogenesis within axons that begins with the merging of organelles derived from the endocytic and autophagic pathways followed by further maturation toward lysosomes that is coupled to their retrograde transport (44)(45)(46)(47)(48)(49). More specifically, there is a high level of constitutive autophagosome biogenesis that occurs within distal regions of axons (46,48,50,51). These autophagosomes fuse with endosomes and acquire endocytic cargos and late endosome/lysosome marker proteins such as LAMP1 (46,48,49).…”
Section: Discussionmentioning
confidence: 52%
“…More specifically, there is a high level of constitutive autophagosome biogenesis that occurs within distal regions of axons (46,48,50,51). These autophagosomes fuse with endosomes and acquire endocytic cargos and late endosome/lysosome marker proteins such as LAMP1 (46,48,49). These initial steps of convergence between the endocytic and autophagic pathways are accompanied by luminal acidification and coincide with a switch toward a predominantly dynein-driven transport in the retrograde direction (48,52).…”
Section: Discussionmentioning
confidence: 99%
“…In the neurons, autophagosomes formed in distal axons mature and fuse with late endosomes and/or lysosomes during transport towards the cell soma. 66 It was shown that disruption of autophagosome transport on microtubules by vinblastin led to the inhibition of autophagosome and lysosome fusion and to accumulation of these vesicles. 3,67 Dynein inhibition by EHNA suppressed fusion of autophagosomes and lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…109 In addition, distal formation and retrograde transport of autophagosomes in axons of primary neurons have been reported and mitochondrial markers have been observed in these autophagosomes. 110 Nevertheless, it is not certain that retrograde transport of an autophagosome to the soma is strictly required as lysosomal markers have also been found to colocalize with autophagosomes in distal axons, implying that lysosomal degradation can be completed outside the soma. 109,110 It bears mentioning that the above studies have looked at the total population of autophagosomes, and the fate of mitophagosomes formed in response to damage in particular have not been analyzed.…”
Section: Mitophagy In Neuronsmentioning
confidence: 99%
“…110 Nevertheless, it is not certain that retrograde transport of an autophagosome to the soma is strictly required as lysosomal markers have also been found to colocalize with autophagosomes in distal axons, implying that lysosomal degradation can be completed outside the soma. 109,110 It bears mentioning that the above studies have looked at the total population of autophagosomes, and the fate of mitophagosomes formed in response to damage in particular have not been analyzed. Understanding the dynamics of damaged neuronal mitochondria and the molecular players of neuronal mitophagy will help elucidate the contribution of mitochondrial dysfunction to neurodegenerative diseases.…”
Section: Mitophagy In Neuronsmentioning
confidence: 99%